ضوابط تقدير حد السرف في زكاة حلي المرأة وتطبيقاتها لدى مؤسسات الزكاة في ماليزيا : دراسة فقهية تحليلية - Siti Nurhafizan Panglima (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research aims to study had al-saraf fi zakat Hulee al-mar'ah (the parameter of what is considered as extravagant quantity of woman's jewellery regarding Zakat), as assessed by Zakat institutions in Malaysia. This research first investigates the institutions' adopted methods in the assessment process, and then discovers as to what extent these methods are considered in Islamic jurisprudence by viewing the jurists' opinions in had al-saraf fi zakat Hulee al-mar'ah. Zakat institutions in Malaysia differ in estimating had al-saraf. The researcher adopts the inductive method in viewing the jurists' opinions about the issue in question, and collecting data from Zakat institutions (official documents, a variety of publications). The researcher uses the analytical approach in analyzing the jurists' opinions and to the extent these opinions are taken into consideration by Zakat institutions in Malaysia. The field study is also adopted through interviews with employees of various Zakat institutions to find out the methods used in estimating had al-saraf fi zakat Hulee al-mar'ah. The researcher concludes that various Zakat institutions in Malaysia – apart from the two Zakat institutions in Kelantan and Perlis states - have estimated the amount of had al-saraf fi zakat Hulee al-mar'ah according to certain parameters, yet they did not agree on one amount. This difference is not unusual, because these institutions follow Shafi'i school, which upholds that 'urf (custom) should estimate had al-saraf, and customs are subject to change according to place and time.